Mucopolysaccharides secreted by the sea slug Elysia crispata incorporate carbon via kleptoplast photosynthesis - Lopes, Diana; Cartaxana, Paulo; Ferreira, Sónia S.; Silva, Maria Inês; Nunes, Margarida; Barata, Joana; Nunes, Cláudia; Cruz, Sónia (Frontiers in Marine Science, 2025)
Some Sacoglossa sea slugs feed on macroalgae and sequester chloroplasts in the cells of their digestive diverticulum. In some species, mostly within the genus Elysia, the stolen chloroplasts – kleptoplasts – remain photosynthetically competent for weeks to months. These sea slugs, like other gastropods, produce a viscous secretion or mucus involved in protection, locomotion, and reproduction. In this study, we profiled the carbohydrate composition of the mucus of the kleptoplast-bearing sea slug Elysia crispata and tracked the incorporation of carbon and nitrogen via stolen chloroplasts. Mucopolysaccharides were mainly composed by uronic acids and galactose with 1→4 glycosidic linkages. Using inorganic 13C-labelled sea water, incorporated carbon was found in the secreted mucus only in the presence of light, mainly in the form of 3-O-methylgalactose, galactose, and fucose. Inorganic 15N in the sea water could be traced in the sea slug tissues and in the mucus in both dark and light, with slightly higher levels found under the latter condition. Results show that inorganic carbon was fixed through photosynthesis in the kleptoplasts of the digestive diverticula, translocated as organic carbon to other animal tissues and incorporated in the secreted mucopolysaccharides. The present study pinpoints the biological relevance of photosynthesis to the metabolism of these remarkable animal-chloroplast symbiotic associations.